Do stones still kill? An analysis of death from stone disease 1999–2013 in England and Wales. (12th February 2016) - Kum, Francesca; Mahmalji, Wasim; Hale, Jemma; Thomas, Kay; Bultitude, Matthew; Glass, Jonathan
Abstract : Objectives: To analyse the trends in the number of deaths attributable to urolithiasis in England and Wales over the past 15 years (1999–2013). Urolithiasis has an estimated lifetime risk of 12% in males and 6% in females and is not perceived as a life‐threatening pathology. Admissions with urinary calculi contribute to 0.5% of all inpatient hospital stays, and the number of deaths attributable to stone disease has yet to be identified and presented. Materials and Methods: Office of National Statistics data relating to causes of death from urolithiasis, coded as International Classification of Diseases (ICD)‐10 N20–N23, was collated and analysed for the 15‐year period from 1999 to 2013 in England and Wales. These data were sub‐categorised into anatomical location of calculi, age, and gender. Results: In all, 1954 deaths were attributed to urolithiasis from 1999 to 2013 (mean 130.3 deaths/year). Of which, 141 were attributed to ureteric stones (mean 9.4 deaths/year). Calculi of the kidney and ureter accounted for 91% of all deaths secondary to urolithiasis; lower urinary tract (bladder or urethra) calculi contributed to only 7.9% of deaths. The data revealed an overall increasing trend in mortality from urolithiasis over this 15‐year period, with an increase of 3.8 deaths/year based on a linear trend ( R 2 = 0.65). Overall, the number of deaths in females was significantly higher than in males (ratio 1.5:1, P < 0.001); kidney and ureteric calculi causing death had a female preponderance (1.7:1, female:male); whereas calculi of the lower urinary tract was more common in males (1:2.2, female:male). Conclusions: Stone disease still causes death in the 21st century in England and Wales. This trend of increasing deaths must be placed in the context of the concurrent rising incidence of urolithiasis in the UK and the number of stone‐related hospital episodes. The primary cause of death relating to complications of stone disease for each individual case should be further investigated to facilitate prevention of complications of urolithiasis.